Optimalisasi Lahan Rawa Melalui Reklamasi Sistem Irigasi dan Drainase di Desa Banyuasin - Hidayatulllah, Muhammad Ridha; Puspitahati, Puspitahati; Syahadan, Syahadan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Hidayatullah, M. R., Puspitahati, P., & Syahadan, S. (2024). Optimization of swamp land through reclamation of irrigation and drainage systems in Banyuasin Village. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 918–928). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Swampland has great potential to be planted, but it is often difficult to make full use of it due to watery environmental conditions and unstable soil. In an effort to increase agricultural productivity, optimizing the use of swamp land is an urgent need. One approach that can be done is to implement an efficient and targeted irrigation system. This study aimed to find out and study how swamp land optimization uses irrigation systems and study the problems and obstacles faced when optimizing swamp land using irrigation systems in Bangka Regency. The method used in this study is an observation method which includes direct observation in the field, interviews with staff, and data recording. The conclusion of this study is that the rice field in Banyuasin Village covers an area of 80 ha with 6 ha being forests and swamps. However, with the existence of swamp land optimization activities, it can increase the planting area by 26 ha so that there are 100 ha of rice paddy land that can be planted with rice, The problems experienced in swamp land are often flooded if it rains excessively and drought if it is dry season, The obstacles faced are, the development of irrigation canal infrastructure which is still not comprehensive in the rice fields of Banyuasin Village, Where it is still in the form of soil excavation only so that water has not optimally flowed to the rice field map. The strategy carried out to overcome these obstacles is to build permanent irrigation canals and reclaim irrigation and drainage canals that have been carried out by the Bangka Regency Food and Agriculture Office.